A changing world - Hyndman, Michael (London : George Allen & Unwin, 1974)
Man's adaptation to the problems of the post-glacial age together with the discovery of farming and its slow spread across Europe to the British Isles. (Bron: covertekst)
Keywords: 062911jpg; Prehistorie